2020
DOI: 10.22271/oral.2020.v6.i4b.1050
|View full text |Cite
|
Sign up to set email alerts
|

Current applications of chitosan nanoparticles in dentistry: A review

Abstract: Nanotechnology is widely used in our day to day life including its use in medicine. Nanostructures are used in innovations or diagnosis of dentistry. Some nano-particles are used for oral disease preventive drugs, prostheses and for teeth implantation. Nano-materials further deliver oral fluid or drugs, preventing and curing some oral disease like oral cancer and maintain oral health care up to a high extent. The nanoparticle like chitosan has anti-microbial, anti-oxidant, and anti-tumor effects. The literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the present study, the use of 5 ml of 0.2% Nano chitosan for 3 minutes was justified by a preliminary study found that applying 0.2% chitosan acetate for 3 minutes was the most effective chelating agent when compared to chitosan prepared with different concentrations and contact times (34) . Moreover, CSNPs have been used to improve the effectiveness of chitosan, where nanomaterials have unique physicochemical properties such as large surface area and enhanced chemical reactivity, when compared to their bulk counterparts (42) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the use of 5 ml of 0.2% Nano chitosan for 3 minutes was justified by a preliminary study found that applying 0.2% chitosan acetate for 3 minutes was the most effective chelating agent when compared to chitosan prepared with different concentrations and contact times (34) . Moreover, CSNPs have been used to improve the effectiveness of chitosan, where nanomaterials have unique physicochemical properties such as large surface area and enhanced chemical reactivity, when compared to their bulk counterparts (42) .…”
Section: Discussionmentioning
confidence: 99%
“…Nano materials provide unique physicochemical characteristics of ultrasmall particle sizes, increased surface area related to mass ration, and improved chemical reactivity compared to their bulk material form (12) . Chitosan nanoparticles have been introduced to mend the root canal disinfection since it showed better antibiofilm capacity and bacterial degradation, and has chelating effect capable to remove the smear layer with the ability to penetrate deeper into the root canal irregularities and dentinal tubules criteria that make it suitable to be used as finishing rinse during root canal irrigation (13) .…”
Section: Introductionmentioning
confidence: 99%
“…The NPs can be synthesized through two approaches; topdown and bottom-up approaches [9]. The top-down approach reduces the size of bulk materials to nanoscale by grinding or etching while the bottom-up approach is the synthesis of nanoparticles involving chemical reactions from small (bio)molecules [10]. Based on previous studies, there were several methods involving chemical reactions in the preparation of the NPs.…”
Section: Introductionmentioning
confidence: 99%